Pengaruh Fraud Diamond Terhadap Kecenderungan Kecurangan Laporan Keuangan pada Koperasi Kredit Sube Huter - Wilhelmina Mitan; Siktania Maria Dilliana; Robertho Tomy Meyer (Peneliti.net, 2021)
This study aims to examine: 1) Influence on Financial Statement Fraud, 2) Effect on Financial Statement Fraud, 3) Effect of Rationalization on Financial Statement Fraud, 4) Influence on Financial Statement Fraud Tendency. This type of research is classified as causal associative research. The population in this study were employees of the Sube Huter Credit Cooperative. Sampling using saturated sampling technique, with the number of respondents as many as 30 people namely Management, Supervisor, Manager, Head of TPK, Head of Division, Finance Staff, and LO Staff. The data collection technique used is by using a questionnaire. The data analysis technique used is multiple regression with the help of the Statistical Package for Social Science (SPSS). The results of this study indicate that pressure, opportunity, rationalization, and ability have no significant effect on the tendency of financial statement fraud either partially or simultaneously